Exploring qur'anic parenting: a religious approach to enhancing children's psychological and moral well-being - Siregar, Husnul Khotimah; Zuhri, Ahmad; Naldo, Jufri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This article explores Qur'anic parenting as a religious approach to improving children's psychological and moral well-being. Qur'anic parenting, grounded in Islamic teachings, emphasizes the cultivation of moral character and psychological resilience in children through the application of principles such as compassion, justice, and wisdom. The article examines how these principles, derived from the Qur'an, can be implemented in modern parenting practices to foster the holistic development of children. Along with the lack of knowledge, attention, and practice of parents regarding parenting in accordance with Sharia, this has an impact on the decline in the quality of children's morals, thus triggering many problems of juvenile delinquency. One of the impacts of this concern is that some people choose not to have children. So of course, every parent needs to know the signs of parenting in the Quran. This research also aims to provide information and understanding of the concept of parenting in the Qur'an. The research method used is library research with a thematic study approach. Collecting several words in the term child then analyzing it and making it in several sub-discussions. The results of this study include the following: The Qur'an has explained in detail about the nature of children and the rights that need to be given to them, which is an indication that parents should apply to them, such as; giving affection, giving good names, being a good example and always giving good advice to children.